Effects of mindfulness on stress, life satisfaction, and savoring beliefs among Hong Kong Chinese adolescents during the COVID-19 pandemic - Lau, Ngar-sze; Cheung, Rebecca Y. M.; Lai, Cheuk Ki Stephanie; Lau, Abby Yan Tung; Fung, Man Ching (Frontiers in Psychology, 2023)
Adolescents all over the world are vulnerable in facing developmental challenges. Recent studies have evidenced that the unexpected interruptions of school learning during the COVID-19 pandemic have raised concerns about the well-being of adolescents. This present study sought to investigate the relationship between mindfulness, stress, savoring beliefs, and satisfaction of life among adolescents in Hong Kong during COVID-19. A total of 240 Hong Kong Chinese adolescents between 15 to 19 years of age (M=15.60; SD=.70) from schools with different religious backgrounds completed an online survey. Findings from hierarchical linear regression indicated that statistically, mindfulness negatively predicted stress and positively predicted life satisfaction and savoring beliefs. Students with faiths did not show any significant differences in mindfulness and other variables in this study. In terms of implications, these findings provide positive evidence that mindfulness may be an important aspect for interventions designed to enhance life satisfaction and savoring beliefs, and reduce stress of adolescents over challenging times. Overall, this study suggests youth service providers to develop effective strategies in schools and communities for further promoting wellbeing and resilience of adolescents.